Manajemen Edukasi Preventif dan Penatalaksanaan Covid-19 Berbasis Home Learning System Pada Remaja - Nian Afrian Nuari; Didit Damayanti; Sony Susanto (Jurnal SOLMA, 2021)
Background: The high number of Novel Coronavirus Diseases (Covid-19) cases in Indonesia has caused the public to need proper education regarding the prevention and management of Covid-19, especially teenagers. Teenagers are part of the community who need to know about Covid management to maintain healthy living behaviours. This preventive management education using the home learning system method is very suitable for use during the pandemic. The purpose of this community service was to increase the knowledge and skills of adolescents in taking preventive measures and the management of Covid-19. Methods: This activity includes two stages of providing education and demonstration using online media. Results: Based on the post-test results, it was found that almost all teenagers had scores of knowledge scores at 8-10 intervals after a preventive education and Covid-19 management based on a home learning system. The results of the skills indicator show that almost all teenagers can knowledge again with a score of 8-10. Conclusion: The application of the Home Learning System is very suitable for students to increase their knowledge and abilities in taking preventive and curative actions independently.